Management of Archery-Based Sport Games to Improve Numeracy and Attention in Elementary School Students: A Sequential Exploratory Mixed-Methods Study - Hendra Setyawan; Widha Srianto; Ismail Gani; Diah Andika Sari; Matsuri; Ratko Pavlovic (Jurnal Penelitian Pendidikan IPA, 2026)
Competency-based learning transformation requires the strengthening of numeracy and attention from elementary school through meaningful, safe, and measurable learning experiences. This study aimed to synthesize scientific evidence on the management of archery-based sport games and to verify its practical relevance through primary questionnaire data. A sequential exploratory mixed-methods design was employed. The first phase consisted of a systematic literature review conducted according to the PRISMA guidelines. A Scopus search identified 170 records, which were screened based on publication year, article type, language, access status, primary data orientation, and relevance to archery, target sports, physical education games, attention, and numeracy integration. A total of 25 articles were included in the narrative synthesis. The second phase was conducted using a five-point Likert-scale questionnaire administered to 25 elementary school physical education students who had experience in archery courses. The results showed very high internal consistency, with Cronbach’s alpha = 0.945. The overall item mean was 4.47 out of 5, the mean total score was 120.80 out of 135 with SD = 10.81, and 96.74% of responses were categorized as positive. The safety and readiness construct obtained the highest mean score (M = 4.75), followed by attention enhancement (M = 4.49), motivation and engagement (M = 4.49), game-based learning design (M = 4.42), numeracy integration (M = 4.38), and implementation feasibility (M = 4.34). The integration of both findings indicates that archery-based games have the potential to serve as a safe, engaging, and measurable physical education strategy for training focus and embedding contextual numeracy activities. However, claims regarding numeracy improvement still require direct experimental testing with elementary school students.